Designing English Teaching Materials for Students of the Food and Beverage Service Study Program based on industry needs - Ratnah, Ratnah; Saputri, Faradillah; Badollahi, Muh. Zainuddin (Journal La Edusci, 2022)
Every student has different needs in learning English, including their needs in the workplace. This research aims to determine the existence of English language skills of students in Food and Beverage Service (FBS) department, identify their English language needs in the workplace, and design English language teaching materials based on their needs in the workplace. This research is a quantitative study by using survey methods. The data collection techniques used were questionnaires, interviews and observations by taking the FBS students who had carried out internship program as the population while the sampling technique used was purposive and accidental sampling by involving 143 respondents. Based on the results of the data analysis, it was found that 1) The existence of English language skills of students in FBS department is at the elementary and pre-intermediate levels, namely 73.42% and speaking skills are the skill they have mastered the most as well as the most difficult skill. And vocabulary and pronunciation are two language components they considered as the most difficult to be understood, 2) The English language needs of FBS students in the workplace show that speaking skills are the most needed skill, namely 76.92%, where all outlets in the FBS departments require language mastery English, namely 68.53%, especially in the restaurant section around 20.98%, 3) English teaching materials designed should be based on students' needs in the workplace by using a priority scale on the learning materials and activities which described in the form of learning plans.